Per-pixel revolution mapping with rectification of the texture projection - Ragragui, Anouar; Chahdi, Adnane Ouazzani; Halli, Akram; Satori, Khalid (2018 International Conference on Intelligent Systems and Computer Vision (ISCV), 2018)
Per-pixel revolution mapping is an image-based modeling and rendering technique or IBMR (Image-Based Modeling and Rendering). It consists of generating very convincing revolved surfaces without polygonization effect, which are displayed interactively by the graphics cards. When it is about the interactivity or about the visual quality, this technique produces satisfactory results. When the revolved surface is created, we observed that the texture did not map in a correct way. In this paper, we presented an improvement of the revolution mapping technique to solve the problem related to the texture mapping.